2018
DOI: 10.1152/ajpcell.00196.2017
|View full text |Cite
|
Sign up to set email alerts
|

The pump, the exchanger, and the holy spirit: origins and 40-year evolution of ideas about the ouabain-Na+ pump endocrine system

Abstract: Two prescient 1953 publications set the stage for the elucidation of a novel endocrine system: Schatzmann's report that cardiotonic steroids (CTSs) are all Na pump inhibitors, and Szent-Gyorgi's suggestion that there is an endogenous "missing screw" in heart failure that CTSs like digoxin may replace. In 1977 I postulated that an endogenous Na pump inhibitor acts as a natriuretic hormone and simultaneously elevates blood pressure (BP) in salt-dependent hypertension. This hypothesis was based on the idea that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 304 publications
(370 reference statements)
0
35
0
2
Order By: Relevance
“…The presence of EO was finally demonstrated with mass spectrometry, nuclear magnetic resonance (NMR) and chromatography, confirming its existence and its identicalness to the plant-derived ouabain [ 27 , 28 ]. Furthermore, it was possible to identify the most important production site of EO in the adrenal cortex [ 29 , 30 ]. All this evidence led to the identification in mammals of numerous endogenous cardiotonic steroids as cardenolides and bufodienolides (as marinobufagenine) [ 31 ].…”
Section: Endogenous Ouabain (Eo) and Na + /K mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of EO was finally demonstrated with mass spectrometry, nuclear magnetic resonance (NMR) and chromatography, confirming its existence and its identicalness to the plant-derived ouabain [ 27 , 28 ]. Furthermore, it was possible to identify the most important production site of EO in the adrenal cortex [ 29 , 30 ]. All this evidence led to the identification in mammals of numerous endogenous cardiotonic steroids as cardenolides and bufodienolides (as marinobufagenine) [ 31 ].…”
Section: Endogenous Ouabain (Eo) and Na + /K mentioning
confidence: 99%
“…EO might be actually considered as a growth-promoting hormone. Indeed, many authors showed that EO is involved in pro-hypertrophic and pro-fibrotic pathways that lead to cardiac remodeling with a negative impact on both cardiac structures and cardiovascular functions [ 30 , 44 ]. The authors also tried to understand how EO might perform the role of a signal transducer.…”
Section: The Correlation Between Endogenous Ouabain and Organ Damamentioning
confidence: 99%
“…In fact, cardenolides have been used medicinally for hundreds of years as common treatments for conditions such as congestive heart failure and cardiac arrhythmias [18]. A growing number of studies have implicated the regulation of Na + , K + -ATPase by putatively endogenous cardenolides in signalling pathways linked to a variety of pathologies including hypertension and cancer [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been asserted that "ouabain is a key factor in the pathogenesis of hypertension and heart failure" [11]. The concept of "endogenous ouabain" (EO) originated in the late 1970s when it was postulated that an endogenous inhibitor of vascular Na/K ATPase might be a natriuretic hormone (NH) causing hypertension [12].…”
mentioning
confidence: 99%
“…These results confirm that there is no endogenous ouabain in human plasma. In a series of publications Mordecai P. Blaustein, who strongly advocates the EO concept, vigorously denies the results of Vogeser's laboratory [11,18,19]. With dubious claims and even unfounded accusations ("edited their raw data", "scientific misconduct") he tries to discredit Vogeser's method.…”
mentioning
confidence: 99%